A Statewide Medication Management System: Health Information Exchange to Support Drug Therapy Optimization by Pharmacists across the Continuum of Care - Pellegrin, Karen; Chan, Francis; Pagoria, Natalie; Jolson-Oakes, Sheena; Uyeno, Reece; Levin, Andrew (Applied Clinical Informatics, 2018)
Background While evidence generally supports the use of medication management technology, systems are typically implemented and evaluated piecemeal rather than as part of a comprehensive model for medication management. Systems to support drug therapy optimization, increasingly a key role of pharmacists in our healthcare system, have not yet been reported.Objective Our objective is to describe the design, implementation, and use of health information technology to support the hospital and community pharmacists' management of medications for high-risk patients statewide in the “Pharm2Pharm” model of care. Our aims were to make it easier for the pharmacists to access information needed to identify and resolve drug therapy problems using best practices for medication management and communicate with other members of the care team.Methods The pharmacist's roles and the medication management processes guided the design of the supporting technology, which was implemented after the Pharm2Pharm model was launched and the pharmacists' technology needs were assessed. Priorities for technology included sending care transition documents from hospital to community pharmacist securely and efficiently, access to medical records, including medications and laboratory results, documentation, and patient tracking. Implementation and use of the technology were documented.Results Communications, medication management, and population management solutions were implemented to support the Pharm2Pharm model. The pharmacists delivering services through this model adopted and meaningfully used this technology to support their work.Conclusion Implementing technology with value outside of the Pharm2Pharm model was a strategic approach to investment. This work emphasizes the importance of shifting the focus of technology from supporting a specific piece of the medication management process to supporting the goal of optimizing medication regimens. Health information exchange systems can provide important technology needed to integrate pharmacists into care teams as they are deployed to improve patient outcomes.
Keywords: drug therapy optimization; pharmacists; medication reconciliation; health information exchange; health information technology